Effect of Salt Substitution on Cardiac Structure and ECG Parameters in Middle-aged and Elderly Hypertensive Patients - Li Che; Ying Zhang; Xia Chen; Haiqing Du; Wei Song; Yinong Jiang (Reviews in Cardiovascular Medicine)
Background: Salt substitution (SS) has been found to reduce blood pressure (BP). However, the impact of SS on cardiac structure, as assessed through ultrasonic cardiogram (UCG) and electrocardiograms (ECG), remains poorly understood. This study aims to evaluate the effects of SS on cardiac structure and ECG parameters. Methods: This 12-month prospective, multi-center, randomized, double-blind study involved hypertensive patients aged 50 to 70 years with office systolic BP (SBP) ranging from 140 to 180 mmHg and diastolic BP (DBP) ranging from 90 to 110 mmHg. A total of 352 patients were enrolled and equally randomized to either the normal salt (NS) group or SS group. Office BP measurements (OBPM) were obtained at baseline and at 3, 6, and 12 months, while home BP measurements (HBPM) were recorded at baseline, 3, 6, 9, and 12 months. Fasting blood, UCG, and ECG parameters were obtained at baseline and at the end of the study. Results: Of the 352 enrolled patients, 322 completed the study. In the SS group, the reductions in systolic OBPM, HBPM, and diastolic HBPM were significantly greater than those in the NS group. Notable cardiac parameter changes included a reduction in QT dispersion (QTd) by –5 ms (–10, 5) in the NS group and –5 ms (–15, 0) in the SS group (p = 0.001); the T wave peak-to-end (Tp-e) value was 0 ms (–5, 10) and –5 ms (–10, 0) (p < 0.001), respectively; and Tp-e/QT was 0 (–0.01, 0.02) and –0.02 (–0.04, 0) (p < 0.001), respectively. Additionally, left atrial diameter (LAD) was 0 mm (–1, 1) and –1 mm (–2, 1) (p < 0.001), and the change in left ventricular mass (LVM) was –2 g (–17.75, 11) and –7 g (–18, 6) (p = 0.035), respectively. Conclusions: This study demonstrates that SS not only significantly decreased LAD and LVM, indicating a significant effect on cardiac structure, but also improves UCG parameters, including reductions in QTd, Tp-e, and Tp-e/QT. These findings highlight the potential of SS as a beneficial intervention in managing cardiac risks in hypertensive patients. Clinical Trial Registration: ChiCTR1800019727. (https://www.chictr.org.cn/showproj.html?proj=31036).